PENGARUH PENGGUNAAN MODEL DISCOVERY LEARNING TERHADAP KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK KELAS XI MIPA DI SMA NEGERI 1 SEKAMPUNG - Ira Anggraini; Handoko Santoso; Agil Lepiyanto (EDUBIOLOCK, 2021)
The teaching and learning process often does not run smoothly, which is influenced by several factors, one of which is caused by the use of the learning model planned by the teacher that does not support students to be able to improve their ability to think creatively independently. The purpose of this study was to determine the effect of the use of discovery learning models on the creative thinking ability of students of class XI MIPA in SMA Negeri 1 Sekampung. This research uses quantitative research. The research to be carried out is a quasi-experimental study with a group pretest-posttest design. Based on the results of the hypothesis test analysis, regarding the effect of discovery learning models on the creative thinking ability of students of class XI MIPA in SMA Negeri 1 Sekampung it can be concluded that the discovery learning models influence the student's creative thinking abilities, evidenced by the relevant hypothesis test result namely t-test that thit (8,17) is greater than tdaf (1,67) in the 0,05 significance level.